Formas de peinados en cabello aplicado por docentes a estudiantes con modelos de trenzas en el Centro Artesanal Armando Coronel Dreshner, cantón El Empalme Provincia del Guayas - Alvarado Segovia, Jacqueline Guadalupe (2015)
Thousands of years ago, hair was seen as a powerful magical element. Even today it is considered as a primitive culture. Hair care is very important, it is seen as an adornment rather than an enhancement to your personality, it plays an important, fundamental and aesthetic role, if we know how to groom ourselves we can look better. It is important to give interest to the care and way of combing, making known the latest inventions to facilitate combing. The mechanisms of hairstyle study a motor behavior oriented to creativity and for it the control of movement of the hands, muscles and joints is required, we can highlight one of the hairstyles as the elaboration of several hairstyles in braids, with different models for beauty of women, which reflects feminine beauty, improves hair presentation and increases self-esteem. This present work is to give importance to the hairstyles of that time that have embellished women today that highlight attitudes according to the occasion and our society.